Efficacy of biofertilizers on the performance of rainfed coriander (Coriandrum sativum) in vertisols - T Yellamanda reddy, Giridhar Kalidasu, C Sarada, (Journal of Spices and Aromatic Crops, 2008)
Biofertilizers are cheap, eco-friendly, improve soil fertility and plant nutrition within shorttime, and are effective components in organic farming. The present study was undertakenwith nine treatment combinations containing Azospirillum Sp., Azatobactor sp. and PSB andcombination of Azospirillum and PSB, Azatobactor and PSB, Vermicompost, Trichoderma viride,100 % inorganic Nitrogen and control in RBD with three replications. Inoculation ofmicroorganisms and FYM @ 5 t/ha applied along with recommended dose of inorganicNitrogen @ 100 % N had shown significant influence on growth parameters when comparedwith absolute control. However, the influence of microorganisms is significant only on numberof secondary branches and number of umbels per plant when compared to 100% N. Plantheight, number of primary and secondary branches were significantly more in treatmentwith 100 % N in combination with Azospirillum, PSB and FYM @ 5 t/ha (66.4 cm, 6.2 and 15.4respectively) than control (58.3 cm, 4.4 and 8.7 respectively). Among all the treatmentcombinations, 100 % N in combination with Azospirillum, PSB and FYM @ 5 t/ha recordedhighest seed yield (1004.0 kg/ha) which is significantly superior to 100% N alone (877.7 kg/ha). In addition to the increase yield, the treatment recorded an incremental Benefit CostRatio of 1.63. The increase in yield in treatments with Azospirillum, PSB and FYM along with100% RDF may be due to better uptake of Nitrogen and Phosphorous and enhanced foodaccumulation.